Design and comparison of nine‐level single‐phase inverters with a pair of coupled inductors and two dc sources. Issue 11 (1st September 2016) - Hashemizadeh‐Ashan, Sasan; Monfared, Mohammad
Abstract : Four different nine‐level single‐phase inverters with coupled inductors are proposed in this study, for the first time. All proposed topologies are based on the well‐known multilevel converters with two separate dc voltage sources in their structure, with some modifications to include a cell with the coupled inductors and a pair of half‐bridge legs. Fewer number of semiconductor devices and dc sources and no need for split capacitors make the proposed inverters very attractive to both researchers and industry. The proposed inverters are compared with other conventional nine‐level topologies from different points of view. Experimental results for these inverters on a low‐voltage test bench are provided to demonstrate the validity of the analytical analysis.